2013
DOI: 10.1590/s1983-40632013000100009
|View full text |Cite
|
Sign up to set email alerts
|

Características produtivas do trigo em função de fontes e doses de nitrogênio

Abstract: A adubação nitrogenada é uma importante prática de manejo em gramíneas e bastante complexa, em função dos diversos fatores que a influenciam, como condições climáticas, sistemas de cultivo, doses e fontes disponíveis. Este trabalho objetivou avaliar o efeito de fontes e doses de nitrogênio (N) em cobertura sobre as características produtivas do trigo (Triticum aestivum L.) cultivado em sistema de semeadura direta, em sucessão à cultura da soja. O experimento foi realizado utilizando-se Latossolo Vermelho distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 12 publications
3
35
0
16
Order By: Relevance
“…No entanto, o fornecimento de N às plantas depende, entre outros fatores, da quantidade de matéria orgânica do solo, da composição dos resíduos vegetais, da expectativa do rendimento e da umidade, aeração e temperatura que interagem entre si nos sistemas de cultivo (Rocha et al, 2008;Siqueira Neto et al, 2010;Costa et al, 2013). As características genéticas das cultivares, condições climáticas e técnicas de cultivo, também atuam sobre a eficiência de uso e aproveitamento do N (Dencic et al, 2011;Prando et al, 2013;Viola et al, 2013).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…No entanto, o fornecimento de N às plantas depende, entre outros fatores, da quantidade de matéria orgânica do solo, da composição dos resíduos vegetais, da expectativa do rendimento e da umidade, aeração e temperatura que interagem entre si nos sistemas de cultivo (Rocha et al, 2008;Siqueira Neto et al, 2010;Costa et al, 2013). As características genéticas das cultivares, condições climáticas e técnicas de cultivo, também atuam sobre a eficiência de uso e aproveitamento do N (Dencic et al, 2011;Prando et al, 2013;Viola et al, 2013).…”
Section: Introductionunclassified
“…Desta forma, estudos da eficiência de uso do N sobre novos genótipos disponíveis são fundamentais para atualizar as recomendações técnicas e disponibilizar tecnologias mais ajustadas trazendo produções economicamente satisfatórias e com menor risco de poluição ambiental (Teixeira Filho et al, 2010;Prando et al, 2013).…”
Section: Introductionunclassified
“…Nitrogen fertilization is decisive for wheat yield, but there are multiple processes interfering with the N use efficiency, such as the characteristics of soil and climate (Prando et al, 2013). The reduced soil moisture decreases N use efficiency, limiting the yield (Mantai et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen (N) is essential to guarantee high yield of the wheat crop (Teixeira Filho et al, 2010;Prando et al, 2013), but is easily leached in rainy years (Teixeira Filho et al, 2010; Mantai et al, 2015) or volatilized in dry years (Rojas et al, 2012;Arenhardt et al, 2015). Thus, N use efficiency by wheat is eventually compromised, decreasing the yield and increasing the losses to the environment (Prando et al, 2013. Technologies that allow to improve yield with greater sustainability are necessary, especially in the increase of N use efficiency in the agricultural processes (Pinnow et al, 2013; Mantai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the plant, the N-fertilizer stimulates vegetative and root growth, with reflex in the absorption of nutrients and production of biomass and grains (Flores et al, 2012); however, nitrogen, along with the favorable meteorological conditions, acts on plant lodging (Bredemeier et al, 2013). Benin et al (2012) and Prando et al (2013) observed, in wheat, that the increment in the N-fertilizer dose favors plant lodging, especially in rainy years. Espíndula et al (2010) comment that the susceptibility to lodging is related to the excessive vegetative growth caused by the nutritional imbalance, reduced resistance of the stem, type of soil and climatic factors, among others.…”
Section: Bmentioning
confidence: 99%